Laporan Keuangan Berdasarkan Standar Akuntansi Keuangan Entitas Mikro pada Usaha Jasa Ika Laundry di Makassar - Nurul Wahdania; Hariany Idris; Samsinar Samsinar (Lembaga Pengembangan Kinerja Dosen, 2025)
(MSMEs) play a strategic role in accelerating national economic growth, yet the majority of business owners still experience difficulties in presenting financial documentation that aligns with established accounting standard criteria. A similar problem is experienced by Ika Laundry located in Makassar, where the financial recording system still uses conventional methods in the form of cash inflow and outflow documentation without standardized report structure. This situation results in minimal comprehensive financial data that can be used to analyze business performance and support business development strategies. The limitation of financial information impacts the difficulty for business owners to conduct objective performance evaluation and make appropriate strategic decisions. This study is focused on developing Ika Laundry's financial reporting system based on the SAK-EMKM as a more systematic, practical, yet accountable framework. The research approach uses descriptive qualitative methods with information collection through structured interviews, field observations, and documentation of transaction activities throughout December 2024. Data analysis was conducted following comprehensive accounting cycle procedures, starting from business transaction identification, general journal preparation, ledger posting, trial balance compilation, adjustment processes, to financial statement finalization. Research results show that before implementation, Ika Laundry did not have adequate financial documentation according to accounting standards. After compilation, three main report components have been produced according to SAK-EMKM, including statement of financial position, income statement, and notes to financial statements. The documentation presents complete information regarding the company's financial condition, covering total assets, equity, revenue, and operational expenses. SAK-EMKM implementation has proven to enhance financial reporting transparency, facilitate objective business performance evaluation, and provide a credible information basis for strategic decision-making in future business development.